2005
DOI: 10.22621/cfn.v119i3.161
|View full text |Cite
|
Sign up to set email alerts
|

Long-distance Movement of a Dispersing Deer Mouse, <em>Peromyscus maniculatus</em>, in the Boreal Forest

Abstract: We report an apparent long-distance, non-homing movement of 3044 ± 60 m made by a dispersing subadult male Deer Mouse, Peromyscus maniculatus, in southeastern Yukon. Our observation is nearly twice the maximum distance previously recorded for non-homing Deer Mice, and apparently the longest dispersal movement recorded for this species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…This pattern suggests a dynamic interplay between localized foraging behaviour and a strong innate tendency toward movement. It corroborates the increasingly well-documented vagility of small mammals (Bowman et al 1999;Maier 2002;Rehmeier et al 2004;Jung et al 2005), which could be a key attribute for population connectivity at broader spatial scales.…”
supporting
confidence: 83%
See 4 more Smart Citations
“…This pattern suggests a dynamic interplay between localized foraging behaviour and a strong innate tendency toward movement. It corroborates the increasingly well-documented vagility of small mammals (Bowman et al 1999;Maier 2002;Rehmeier et al 2004;Jung et al 2005), which could be a key attribute for population connectivity at broader spatial scales.…”
supporting
confidence: 83%
“…This 4287 ± 10 m single-season, non-homing movement by an adult male Deer Mouse exceeds movements of 3044 ± 60 m and 1768 m reported by Jung et al (2005) and Bowman et al (1999) in similar habitat. Both Jung et al (2005) and Bowman et al (1999) reported long-distance movements of subadult male Deer Mice in autumn that were presumed to be dispersal from natal range.…”
mentioning
confidence: 41%
See 3 more Smart Citations